κ-Opioid Receptor Is Colocalized in GnRH and KNDy Cells in the Female Ovine and Rat Brain - Weems, Peyton W. (Endocrinology, 2016)
Kisspeptin-neurokinin B-dynorphin (KNDy) cells of the hypothalamus are a key component in the neuroendocrine regulation of GnRH secretion. Evidence in sheep and other species suggests that dynorphin released by KNDy cells inhibits pulsatile GnRH secretion by acting upon κ-opioid receptors (KOR). However, the precise anatomical location and neurochemical phenotype of KOR-expressing cells in sheep remain unknown. To this end, we determined the distribution of KOR mRNA and protein in the brains of luteal phase ewes, using an ovine specific KOR mRNA probe for in situ hybridization and an antibody whose specificity we confirmed by Western blot analyses and blocking peptide controls. KOR cells were observed in a number of regions, including the preoptic area (POA); anterior hypothalamic area; supraoptic and paraventricular nuclei; ventromedial, dorsomedial, and lateral hypothalamus; and arcuate nucleus. Next, we determined whether KOR is colocalized in KNDy and/or GnRH cells. Dual-label immunofluorescence and confocal analysis of the KNDy population showed a high degree of colocalization, with greater than 90% of these neurons containing KOR. Surprisingly, GnRH cells also showed high levels of colocalization in sheep, ranging from 74.4% to 95.4% for GnRH cells in the POA and medial basal hypothalamus, respectively. Similarly, 97.4% of GnRH neurons in the POA of ovariectomized, steroid-primed female rats also contained immunoreactive KOR protein. These findings suggest that the inhibitory effects of dynorphin on pulsatile GnRH secretion may occur either indirectly by actions upon KOR within the KNDy population and/or directly via the activation of KOR on GnRH cells.